Determinants of Vaccination Dropout among Children in Urban Slums of Lucknow: A Cross-Sectional Study - Kumar, Santosh; Agarwal, Monika; Kumar H, Dinesh (National Journal of Community Medicine, 2025)
Context: Immunization is one of the most effective public health interventions to prevent infectious diseases and reduce childhood mortality. Urban slums in cities like Lucknow are characterized by overcrowded living conditions, limited access to healthcare, poor sanitation, and socioeconomic disadvantages. The aim was to determine the vaccination dropout rate among children aged 0-24 months in an urban slum of Lucknow and to assess the barriers to vaccination faced by families living in urban slums. Methods and Material: Community-based cross-sectional study among 320 children (0-24 months) residing in 16 randomly selected urban slums and 20 children were chosen randomly for participation within each selected slum in Lucknow, Uttar Pradesh. Multi-stage random sampling was applied pre structured, semi structured interview schedule was used to collected the data along with conformation of immunization status from MCP card and chi square test was used to association and p<0.05 considered significant. Results: Overall dropout rates ranged from 10.07% at birth to the cumulative dropout increased to 19.79 percent at 9 months. Significant associations were found between dropout and child sex, caste and delivery type. Children born at home 56.25% had higher dropout rate compared to institutional births 20%. Conclusions: Despite high institutional delivery rates and MCP card coverage, barriers such as parental literacy, healthcare access, and economic constraints persist.